Evaluation of HCFeMn and SiMn Slag Tapping Flow Behaviour Using Physicochemical Property Modelling and Analytical Flow Modelling - Pistorius, Chris (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.